The strategic importance of oil and gas in the eastern Mediterranean in light of regional and international competition - Kaitan, Wisam (Al-Adab Journal, 2024)
This research aims to know the strategic importance enjoyed by the eastern Mediterranean region, which is considered one of the vital and strategic regions in the world, due to the great natural resources it contains of oil and gas on the one hand, and its geographical location that connects most parts of the world on the other hand, which is a vital corridor No oil and gas supplies to Europe and the world. According to the statements published by the US Geological Survey in 2010, according to which the region contains huge resources of oil and gas, estimated at about (10 trillion cubic meters) of gas and 1.7 billion barrels of oil reserves, whose value ranges between 700 billion and 3 trillion dollars according to the changing crude prices, and this recent discovery has made it a central region for future energy and the main and economic goal of the regional and global powers, so the differences, insecurity and conflicts between the countries of the eastern Mediterranean region, such as the Turkish-Cypriot and the Israeli-Lebanese conflict, in addition to that tension in relations The Egyptian-Turkish, has kept the region away from building a stable environment for energy investment in it, which prompted the formation and formation of alliances and blocs between the countries of the Eastern Mediterranean region and other regional and international parties in order to control and win this vital region, and that this competitive scene has become the most expressive evidence of the map of alliances The new regionalism in the region and the struggle of the regional centers over these large oil and gas resources, whose productivity exceeds the level of Gulf and Russian production. The research dealt with four topics preceded by an introduction and a theoretical framework, where the first topic dealt with the geographical location of the eastern Mediterranean region and its strategic, political, military and economic security importance, while the second topic dealt with regional and international actors in the eastern Mediterranean region, while the third topic dealt with the regional conflict over the demarcation of borders The navy in the eastern Mediterranean. As for the fourth topic, it dealt with the future of the regional conflict in the eastern Mediterranean. The research concluded with the most important conclusions.